Advances in FRP Composites in Civil Engineering c - Ye, Lieping; Feng, Peng.; Yue, Qingrui; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
"Advances in FRP Composites in Civil Engineering" contains the papers presented at the 5th International Conference on Fiber Reinforced Polymer (FRP) Composites in Civil Engineering in 2010, which is an official conference of the International Institute for FRP in Construction (IIFC). The book includes 7 keynote papers which are presented by top professors and engineers in the world and 203 papers covering a wide spectrum of topics. These important papers not only demonstrate the recent advances in the application of FRP composites in civil engineering, but also point to future research endeavors in this exciting area. Researchers and professionals in the field of civil engineering will find this book is exceedingly valuable. Prof. Lieping Ye and Dr. Peng Feng both work at the Department of Civil Engineering, Tsinghua University, China. Qingrui Yue is a Professor at China Metallurgical Group Corporation.
Vol. I FRP for Future Structures: Keynote Papers -- FRP Materials and Sustainability -- All FRP Structures -- FRP Hybrid Structures and Concrete-Filled FRP Tubes -- Smart FRP Structures -- Concrete Structures Reinforced or Prestressed with FRP -- Long-Term Performance -- Fire, Impact and Blast Loading -- Educations, Applications and Design Guidelines -- Vol. II FRP Strengthening Structures: Bond and Interfacial Stresses Between FRP and Concreter -- Confinement of Concrete by FRP in Compression -- Flexural Strengthening of Concrete Beams and Slabs -- Shear Strengthening of Concrete Beams -- Strengthening of Concrete Columns, Walls and Frames -- Strengthening of Steel Structures -- Strengthening of Masonry and Timber Structures.
Keywords: Engineering; Building construction; Engineering; Building Construction; Building Materials; Ceramics, Glass, Composites, Natural Methods